A systematically derived exposure assessment instrument for Chronic Hypersensitivity Pneumonitis - Barnes,H; Morisset,J; Molyneaux,P; Westall,G; Glaspole,I; Collard,HR; CHP,Exposure Assessment Collaborators (Chest, 2020)
BACKGROUND: Chronic hypersensitivity pneumonitis (CHP) is an immune mediated interstitial lung disease, caused by inhalational exposure to environmental antigens, resulting in parenchymal fibrosis. By definition, a diagnosis of CHP assumes a history of antigen exposure, but only half of all patients eventually diagnosed with CHP will have a causative antigen identified. Individual clinician variation in eliciting a history of antigen exposure may affect the frequency and confidence of CHP diagnosis. METHODS: A list of potential causative exposures were derived from a systematic review of the literature. A Delphi method was applied to an international panel of ILD experts, to obtain consensus regarding technique for the elicitation of exposure to antigens relevant to a diagnosis of CHP. The consensus threshold was set at 80% agreement, and median ≤ 2, IQR = 0 on a five-point Likert scale (1: strongly agree, 2: tend to agree, 3: neither agree nor disagree, 4: disagree, 5: strongly disagree). RESULTS: In two rounds, 36/40 experts participated. Experts agreed on 18 exposure items to ask every patient with suspected CHP. Themes included CHP inducing exposures, features that contribute to an exposure's relevance, and quantification of a relevant exposure. Based on the results from the literature review and Delphi process, a CHP exposure assessment instrument was derived. Using cognitive interviews, the instrument was revised by ILD patients for readability and usability. CONCLUSIONS: This Delphi survey provides items that ILD experts agree are important to ask in all patients presenting with suspected CHP and provides basis for a systematically derived CHP exposure assessment instrument. Clinical utility of this exposure assessment instrument may be affected by different local prevalence patterns of exposures. Ongoing research is required to clinically validate these items and consider their impact in more geographically diverse settings.